The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/cncr.25836
|View full text |Cite
|
Sign up to set email alerts
|

Survival after complete surgical resection of multiple metastases from renal cell carcinoma

Abstract: BACKGROUND: Although a role for resection of solitary metastases from renal cell carcinoma (RCC) has been described, the utility of surgery in patients with multiple sites of disease has been less well defined. The authors report the survival of patients who underwent complete metastasectomy for multiple RCC metastases. METHODS: The authors identified 887 patients who underwent nephrectomy for RCC between 1976 and 2006 who developed multiple metastatic lesions. The impact of complete metastasectomy on survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(243 citation statements)
references
References 119 publications
7
225
1
8
Order By: Relevance
“…We also acknowledge that there are biological differences between subjects with distant metastases who undergo metastasectomy and subjects ineligible for metastasectomy. Patients with high-volume disease, rapid progression or poor performance status are less likely to undergo metastasectomy [35,36]. Conversely, the presence of pancreatic metastases in RCC is associated with a more indolent clinical course [37].…”
Section: Discussionmentioning
confidence: 99%
“…We also acknowledge that there are biological differences between subjects with distant metastases who undergo metastasectomy and subjects ineligible for metastasectomy. Patients with high-volume disease, rapid progression or poor performance status are less likely to undergo metastasectomy [35,36]. Conversely, the presence of pancreatic metastases in RCC is associated with a more indolent clinical course [37].…”
Section: Discussionmentioning
confidence: 99%
“…All studies were retrospective and non-randomised, leading to the high risk of bias associated with non-randomisation, patient attrition, and selective reporting. With the exception of one study, 12 all studies were substantially underpowered. Regarding confounding, about half of studies reported adequate data on age and sex.…”
Section: Local Therapies For Brain Metastasesmentioning
confidence: 99%
“…No randomised controlled trials or prospective non-randomised comparative studies were identifi ed. Eight studies assessed local treatments of metastases from renal cell carcinoma in various organs, 12,24,26,27,[29][30][31][32] of which the most common sites were lung, bone, liver, and brain, and less common sites were pancreas, adrenal gland, lymph nodes, thyroid gland, spleen, ethmoid sinus, and skin (table 1). Other studies also assessed local treatments for metastases from renal cell carcinoma in bone (including the vertebrae), 33 29 used treatment beforehand.…”
Section: Review Findingsmentioning
confidence: 99%
See 2 more Smart Citations